Systematic Analysis of Zakat Distribution Models in Modern Islamic Finance - Mukhid Mukhid (Islamic Studies Journal (ISLAM), 2024)
The zakat distribution model in modern Islamic finance faces significant challenges in the era of digitalization, especially related to efficiency, transparency and trust. This research aims to identify the main challenges in implementing the zakat distribution model in the digital financial era using a systematic literature review approach. This method involves a systematic analysis of relevant literature to evaluate the effectiveness of both traditional and digital-based zakat distribution models. The research findings reveal that, although digital technology offers great potential to increase transparency and efficiency, challenges such as lack of user trust and transparency in reporting still need to be overcome. The implications of this research include the need to reform the zakat distribution model to integrate digital technology and improve governance, with the hope of maximizing the impact of zakat in poverty alleviation and sustainable development. This research provides important insights for policy makers and practitioners to design zakat distribution strategies that are more adaptive and responsive to the digital era.